Dermatodaxia (wolf-Biter) of Both Hands - Thamir Kubaisi (Al-Anbar Medical Journal, 2023)
A 14-year-old healthy boy presented to the Dermatology clinic with asymptomatic multiple lichenified firm papules with calluses formation, and skin dyspigmentation, involving the dorsum of both hands and the distal part of the forearms (Panel A and B). The condition was associated with fine scales and sluffing of the cuticles and the proximal nail fold of several fingers (Panel C). The condition started 2 years ago, as a result of history of a frequent compulsive habit of eating and chewing the involved parts of the body without ingestion. The patient became relaxed and enjoyed himself, especially after a stressful event. He demonstrated a skin thickening in this instance without a wound or an ulcer. The compulsion affected the cuticles of several fingers and did not associate with other known body-focused repetitive performances. A diagnosis of dermatodaxia was made. Dermatodaxia describes as an individual who eats his skin. It is a body-focused repetitive behavior and is classified in the group of obsessive-compulsive disorders. Previously named wolf-biter, because angry or trapped wolves will bite themselves. Other synonyms are chewing pads and dermatophagia. The patient was referred to a psychiatrist for further behavioral management. Meanwhile, he advised keeping the involved skin clean and enclosed with dressings like bandages until it heals.